Urgensi Bahasa Arab dalam Pembelajaran di Program Studi Ilmu Hadis UIN Sumatera Utara Medan - Siregar, Nasrun Salim (SHAHIH (Jurnal Ilmu Kewahyuan), 2023)
The Quran and Hadith as the main source of Islamic teaching and both of them are sources that cannot be doubted when it comes to analyzing the essence of Islam and written in Arabic, so that those who are interested in the Quran and Hadith cannot deny the role of Arabic in achieving an accurate understanding of hadith. This study aims to analyze the urgency and influence of learning Arabic for Hadith students at the Faculty of Ushuluddin and Religious Studies, State Islamic University of North Sumatra, Medan. The research method is a descriptive approach with interviews, online questionnaires and observation. The study concluded that 94.4% of the hadith study program students stated that Arabic language knowledge is very important in order to achieve an understanding of hadith and happy to learn it. However, only 44.4% of students had no problems learning Arabic at all and 8.3% of their students feel that learning Arabic is a very problem and other than that only experienced a few problems in learning Arabic. Besides that, 77.7% of students think that learning Arabic has a good impact as an introduction to understanding hadith.